Different Body Fluid Biopsies for Detecting Minimal Residual Disease in Lung Cancer: a Review of the Latest Advances - YAN Xing, LIU Shanmei, LIU Changhong (Zhongguo quanke yixue, 2023)
Post-treatment recurrence is a major difficulty in the treatment of lung cancer, one of the deadliest cancers worldwide. Minimal residual disease (MRD) as a "bridgehead" for the recurrence of solid tumors, is described as the presence of free circulating tumor cells or other tumor cell derivatives in the biological fluid of patients without any clinical cancer symptoms after the primary tumor treatment. China recently issued its first Consensus on the Detection and Clinical Application of MRD in Lung Cancer, aiming at improving the postoperative individualized treatment for lung cancer patients in accordance with the MRD status detected by the liquid biopsy. We reviewed the latest advances in the use of several most widely used body fluids (peripheral blood, urine, saliva, sputum and pleural effusion) in the detection of MRD in lung cancer, and discussed their values in guiding the precise treatment of MRD in lung cancer.